(untitled) (International Journal of Engineering and Computer Science, 2015)
iSearch (Intelligent Search) is an enterprise search solution developed using Apache SOLR. iSearch system index data and documents from a variety of sources such as: file systems, intranets and document management systems. As the data in enterprise is becoming massive so iSearch helps people to seek the specific information they need of any rich text file format from anywhere inside their company. iSearch identifies and enables specific content across the enterprise to be efficiently searched, and displayed only to authorized users.